2018
DOI: 10.3390/ijerph15122763
|View full text |Cite
|
Sign up to set email alerts
|

Exploring General Practitioners’ Views and Experiences of Providing Care to People with Borderline Personality Disorder in Primary Care: A Qualitative Study in Australia

Abstract: The prevalence of people seeking care for Borderline Personality Disorder (BPD) in primary care is four to five times higher than in the general population. Therefore, general practitioners (GPs) are important sources of assessment, diagnosis, treatment, and care for these patients, as well as important providers of early intervention and long-term management for mental health and associated comorbidities. A thematic analysis of two focus groups with 12 GPs in South Australia (in discussion with 10 academic, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 34 publications
0
43
0
Order By: Relevance
“…A total of 29 papers (drawing on 27 unique datasets) were eligible for inclusion (37, 43-70) (Fig 1), representing perspectives from at least 550 clinicians. Clinicians represented a variety of professions and included psychologists, social workers, psychiatric nurses, occupational therapists, psychiatrists, family doctors (known as General Practitioners or ‘GPs’ in the UK) and counsellors (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 29 papers (drawing on 27 unique datasets) were eligible for inclusion (37, 43-70) (Fig 1), representing perspectives from at least 550 clinicians. Clinicians represented a variety of professions and included psychologists, social workers, psychiatric nurses, occupational therapists, psychiatrists, family doctors (known as General Practitioners or ‘GPs’ in the UK) and counsellors (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Consulting with consumers regarding the support they receive, and offering to include peer support in treatment plans is recommended [42]. Further, increasing the availability and accessibility of peer support for both consumers with BPD and their carers is important, including making health professionals aware of peer support options to inform referrals [51].…”
Section: Discussionmentioning
confidence: 99%
“…This complex set of circumstances has led to uncertainty and controversy amongst mental health professionals in disclosing a diagnosis of BPD to an individual, especially adolescents, due to concern for potential stigmatizing effects (Ring & Lawn, 2019 ; Wlodarczyk et al., 2018 ). However, recent research has shown that disclosing the diagnosis to the individual assists them in understanding their experiences and in receiving effective treatment (Courtney & Makinen, 2016 ; Kaess et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%